Classifying the causes of morbidity and error following treatment of facial fractures. Issue 3 (April 2022) - Luo, Jie; Wu, Eiling; Parmar, Sat; Breeze, Johno
Abstract: Analysing morbidity and using this to improve the quality of patient care is an important component of clinical governance. Several methods of data collection and clinical analysis have been suggested, but to date none have been widely adopted. All adult patients sustaining facial fractures were prospectively identified between 01 March 2019 and 28 February 2020, and matched to those who required a return to theatre for surgical complications. Morbidity resulting in a return to theatre was determined using the Clavien-Dindo classification and the Northwestern University error ascribing method. During this period, return to theatre occurred for 33/285 (11.6%) procedures and 23/173 (13.3%) of patients being treated for facial fractures. According to the 27 procedures discussed, Clavien-Dindo Grade IIIb was most commonly found (20/27). Error in judgement (13/35) and nature of disease (12/35) were ascribed as the most common causes of error. Presence of a consultant was associated with increased odds of a return to theatre (p = 0.014). Standardised national data collection of morbidity and error is required for comparisons of outcomes within a single institution or between institutions. To the best of our knowledge, this is the first paper to utilise these widely used methods of morbidity analysis for facial fracture surgery. We would recommend further development of an error analysis method that is more specific to complications from facial fracture surgery.